Different facets of aging in human mesenchymal stem cells - Wagner, Wolfgang; Ho, Anthony Dick; Zenke, Martin (Tissue engineering. Part B, Reviews, 2010)
Mesenchymal stem cells (MSCs) have to be culture expanded to gain relevant cell numbers for therapeutic applications. However, within 2–3 months the proliferation rate of MSCs decays until they ultimately reach a senescent state. This is accompanied by enlarged morphology, reduced expression of surface markers, and decreased differentiation potential. ...